Correlational Effect between Orotracheal Intubation and Dental Changes: A Longitudinal Study - Hirata, Francielle Carneiro; Bottesini, Victor Cavallaro [UNESP]; Calone, Iris Sawazaki; Imparato, José Carlos Pettorossi; Duarte, Danilo Antonio (Sciencedomain International, 2024)
Aims: The aim of this study was to investigate the relationship between prolonged orotracheal intubation and the onset of oral abnormalities, such as dental enamel defects, in preterm infants. Study Design:  This was a cohort study. Therefore, it was conducted as a correlational, observational and prospective study. Place and Duration of Study: This study was conducted at the Neonatal Intensive Care Unit of University Hospital of Western Paraná (HUOP). The study was performed between December 2022 and July 2024. Methodology: This was a prospective observational cohort study of 26 preterm infants, of whom 61.5% were boys and 38.5% were girls. The mean gestational age was 30.4 weeks, and the mean birth weight was 1,420.2 g. The infants were clinically monitored until eruption of the deciduous teeth, and data on neonatal factors, such as the time of intubation, and maternal factors, such as the type of delivery, were collected. Results: Statistical analysis revealed that 26.9% of the babies had enamel defects, which affected mainly the maxillary incisors. There was a significant correlation between lower birth weight and longer duration of intubation, suggesting that lower birth weight babies tend to require longer ventilatory support, increasing the risk of enamel defects. Conclusion: Prolonged intubation is a relevant factor for the development of dental abnormalities in preterm infants, highlighting the importance of early dental follow-up to prevent complications. Despite these limitations, such as the small sample size and the lack of standardized diagnostic criteria for these defects, further studies are suggested to deepen the understanding and improve preventive strategies for these children.